2003
DOI: 10.1177/154405910308200808
|View full text |Cite
|
Sign up to set email alerts
|

Single-nucleotide Polymorphism in the CD14 Promoter and Periodontal Disease Expression in a Japanese Population

Abstract: It has been reported that there is a relationship between a single-nucleotide polymorphism (SNP) in the promoter region of the CD14 gene at position -159 (C-->T) and infectious diseases. The aim of the present study was to test the hypthesis that expression of this SNP correlates with periodontal disease in a Japanese population. The CD14 genotype was determined in 163 subjects with periodontitis and in 104 age- and gender-matched control subjects without periodontitis. The genotype distribution and allele fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 29 publications
1
32
3
Order By: Relevance
“…49 CD14 may be especially useful as a marker if future therapies alter the CD14/TLR4 signaling pathway. In addition, it remains to be determined whether functional polymorphisms within CD14 gene (e.g., its promoter) 50 influence specific PKD outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…49 CD14 may be especially useful as a marker if future therapies alter the CD14/TLR4 signaling pathway. In addition, it remains to be determined whether functional polymorphisms within CD14 gene (e.g., its promoter) 50 influence specific PKD outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies have investigated the CD14 -260 polymorphism in Caucasian CP subjects (Table 11), but the results are conflicting. Two studies found an association with the N -allele and another study with the R -allele whereas five studies did not find any association with the CP susceptibility [87, 93]. …”
Section: Candidate Genes In Relation To Chronic Periodontitis (Cp)mentioning
confidence: 99%
“…Recent case-control studies of our group [7][8][9][10][11][12][13][14][15][16] in Japanese population are summarized in Table 2 and Fig. 1.…”
Section: Aggressive Periodontitismentioning
confidence: 96%